Toponymic Study of Waterfall Names on Lombok Island - Wahyu Hidayat; Mahsun Mahsun; Saharudin Saharudin; Ahmad Sirulhaq (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study aims to describe the lingual form, meaning, and category of toponyms in the naming of waterfalls on Lombok Island. Research on the study of toponymy of waterfall names on Lombok Island is important to study as a basis for efforts to find out and preserve local wisdom based on linguistics in the region. The research method used is a descriptive approach with the listening, speaking, and documentation methods. The data in this study come from primary and secondary sources. Primary sources include community leaders, cultural figures, and local village traditional leaders. While secondary sources include books, journals, official documents, and other sources. The data in this study are the names of waterfalls located on Lombok Island. The results of this study include the following. First, the lingual form in word formation. The lingual form is a noun composition consisting of a combination of nouns, noun verbs, noun adjectives, and noun adverbials. Second, the meaning of the naming consisting of cultural meaning, contextual meaning, and lexical meaning. Third, the categorization of toponymic aspects in the form of manifestation aspects, social aspects, and cultural aspects. The relevance of culture or language in this study can be found in the mindset of the community in naming waterfalls. The basis for naming given by the community, namely: naming based on pools, water, flora and fauna, myths or culture, and location. This represents that culture and language in the study of naming waterfalls in Lombok have relevance between the two.